As reformas previdenciárias pós-Constituição de 1988: aprimoramento ou desmonte da Seguridade Social? - Croches, Rodrigo Gama (2014)
Starting from the Social Security system outlined in the Brazilian Constitution of 1988, this study aims to examine the content, the fundamentals and the impact of the constitutional reforms in the social security, specifically the amendments nº 20/98, nº 41/03 and nº 47/05, as well as the consequences in the infraconstitutional legislation system, concerning its consolidation, distortion and/ or disassemble. Moreover, considering the national historic context related to the theme in analysis, the study will discuss the political and economic circumstances that resulted in (dis)articulation of the precepts, principles, social rights and social security garantees originally set out in the CF/88.